KEBERKESANAN PROGRAM KEDAP KPM DAN KEDAP JAKOA DARI PERSPEKTIF PENGURUSAN PROGRAM: SATU PERBANDINGAN - Md Saleh, Halif; Mustapha, Ramlee (Journal of Techno-Social, 2016)
The study aims at evaluating the effectiveness of non-formal education for adults aborigines in Malaysia which includes ‘the adult Classes For Parents of Aborigines Students and Indigenous’ Programme (KEDAP KPM) organised by the Ministry of Education and Adult Classes of Aborigines Indigenous (KEDAP JAKOA) organised by Department of Aborigines Development Malaysia. The study adopted the programme analysis approach where the data were gathered through questionnaires. The respondents for KEDAP KPM consisted of 136 people representing the administrator and the respondents representing KEDAP JAKOA were 36 administrators. All respondents were selected using random sampling. The data of the study were analysed using the SPSS (Statistical Package for the Social Sciences) 19.0 and the data acquired from the unstructured questionnaires were analysed using the domain analysis. The findings of the study unveiled that the administrator of the programme, students and teachers agree that the programmes were conducted efficiently with the min value score between 3.68 -5.00. However, based on the one way ANOVA Test, 2 out of 4 null hypotheses were rejected. The Pearson Correlation Test showed that the input aspect of the programme such as the planning, curriculum, and teacher’s training, facilities, information sharing and financial sources together with the output aspect such as the teaching process, teaching and learning method have significant impact to the outcome aspect of the programme. On the other hand, the Double Regression Analysis discovered that the teaching process, the student centred teaching method, planning and implementation, teacher’s training and financial sources are the determinant factors to the outcome aspect of KEDAP KPM outcome. The determinants for the development of outcome aspect for KEDAP JAKOA programme consist of curriculum aspect and the student centered learning method.